Social determinants and individual health-seeking behaviour among women in Kenya: protocol for a breast cancer cohort feasibility study. Issue 1 (28th January 2019) - Gakunga, Robai; Ali, Zipporah; Korir, Anne; Kinyanjui, Asaph Wang'ombe; Ochieng', Emily; Gikaara, Nancy; Maluni, Florence; Subramanian, Sujha
Abstract : Introduction: A catastrophic 35% increase in the burden of breast cancer in Kenya has been predicted by 2025. Mitigating this burden is critical, and local research is necessary to generate the evidence to inform policy, public health and medical practice. Most of the knowledge available has been derived from studies in high-income countries that are not directly applicable due to economic, social, cultural and ethnic differences. At the time of writing this paper, we had no knowledge of any longitudinal cohort studies in sub-Saharan Africa of both breast cancer survivors and a matching cohort of women who have never had a diagnosis of cancer. We aim to assess feasibility of cohort studies in Kenya that consider clinical characteristics social determinants and individual health seeking behaviour. Methods and analysis: This study aims to inform best practices for initiating a longitudinal cohort study in Kenya. It is a two-pronged, prospective mixed methods study of women with and without a diagnosis of breast cancer with baseline data collection and one follow-up data collection approximately 3 months later by telephone. Quantitative and qualitative data will be collected concurrently, analysed separately and together to enrich understanding of concepts by triangulation. We aim to include 800 women aged 30–60 years: 400 in the survivorship cohort and 400 in the non-cancer cohort. Two focus group discussions from each cohort will be carried out to enhance understanding of concepts and to guide recommendations. Ethics and dissemination: Independent ethical approval was obtained from Kenyatta National Hospital-University of Nairobi Ethics and Research Committee and the Research Triangle Institute International. Only consenting participants will be enrolled. Counselling support, debriefing discussions and referrals for formal support services will be available for both participants and research assistants. Findings will be disseminated through publications, websites and presentations.